Birds, feather-degrading bacteria and preen glands: the antimicrobial activity of preen gland secretions from turkeys (Meleagris gallopavo) is amplified by keratinase. Issue 9 (12th June 2018) - Braun, Markus Santhosh; Sporer, Frank; Zimmermann, Stefan; Wink, Michael
Abstract: The function of uropygial glands (preen glands) has been subject to controversial debates. In this study, we evaluated the antimicrobial potential of preen gland secretions of turkeys ( Meleagris gallopavo ) against 18 microbial strains by means of diffusion tests, broth microdilutions, checkerboard assays and time-kill curves. Furthermore, we tested the hypothesis that lipids exert direct antimicrobial effects on pathogens. Moreover, we checked for mutualistic relationships between the preen gland bacterium Corynebacterium uropygiale with its hosts. We found that preen gland secretions significantly inhibited the growth of a broad spectrum of bacteria and fungi, particularly when combined with keratinase. Combinations effectively killed multidrug resistant microorganisms in a strongly synergistic manner. Since feather-degrading microorganisms (FDM) express keratinase and thereby disrupt the integrity of the plumage, our data suggests that preen gland secretions of turkeys are specifically activated in the presence of FDM, and specifically eliminate FDM from feathers. However, antimicrobial effects did not originate from lipids, but were mediated by highly polar compounds which might be antimicrobial peptides (AMPs). Finally, C. uropygiale is apparently not involved in the antimicrobial activity of preen gland secretions of turkeys. In conclusion, our results suggest that turkeys can antagonize FDM by amplifying the antimicrobial properties of their preen gland secretions. Abstract : Keratinase activates the antimicrobial potential of preen gland secretions.